Analysis of ultrashort-chain and short-chain (C1 to C4) per- and polyfluorinated substances in potable and non-potable waters - Shun-Hsin Liang; Justin A. Steimling; Mike Chang (Journal of Chromatography Open, 2023)
Ultrashort-chain (USC) per- and polyfluoroalkyl substances (PFAS) are small and very polar compounds with carbon chain lengths of less than C4. Their ubiquitous occurrence in aquatic environments has become a major concern in parallel to long chain PFAS contamination. The high polarity of USC PFAS challenges current analytical practices based on reversed-phase liquid chromatography due to insufficient chromatographic retention. In this study, a fast and reliable LC-MS/MS method was developed for the analysis of C1 to C4 PFAS including trifluoroacetic acid (TFA), perfluoropropanoic acid (PFPrA), perfluorobutanoic acid (PFBA), trifluoromethanesulfonic acid, perfluoroethanesulfonic acid, perfluoropropanesulfonic acid, and perfluorobutanesulfonic acid utilizing a hybrid HILIC/ion exchange column. Three different water samples (tap water, bottled spring water, sewage treatment wastewater) were chosen for method validation to demonstrate the applicability of developed analytical method for the measurement of C1 to C4 PFAS in both potable and non-potable waters. A direct injection workflow was evaluated by accuracy and precision analysis of fortified water samples. Accurate quantification was achieved using calibration standards prepared in reverse osmosis water at the range of 20 to 800 ng/L for TFA, 5.0 to 800 ng/L for PFPrA and PFBA, and 2.5 to 800 ng/L for sulfonic acid PFAS. The average recoveries of fortified samples among three water samples were from 86.6% to 107%, and the relative standard deviation ranged from 1.62% to 10.7%. Additional drinking waters and wastewaters collected from various source waters were tested to further demonstrate that the established workflow is suitable for accurate quantification of C1 to C4 PFAS in a variety of water matrices.